Fortification of freshwater mussels flour in bakpao wrap processing - Hayati, Mardiah; Sari, N Ira (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study was conducted to determine the effect of fortification freshwater mussels.The method used in this study was experimental method, namely the production of bakpaowrap with fortification of different freshwater mussels flour 0; 5%; 10%; and 15%, 20%.Observations were organoleptic (appearance, taste, aroma, texture) and proximate analysis(moisture, protein, fat, ash, carbohydrates). The results showed that treatment B1 (5%addition of freshwater mussels flour) was the best treatment for organoleptic parameterswith consumer acceptance rate 93.8% with 4.75% criteria likes and dislikes. With a watercontent of 31.59 value, protein 21:21, ash 2:54, fat 5.89, carbohydrates 38.77.Keywords: freshwater mussels, freshwater mussels flour, bakpao wrap